The impact of financial parameters on agricultural cooperative and investor-owned firm performance in Greece - Sergaki P.; Semos A. (Food quality products in the advent of the 21st century: production, demand and public policy, 2005)
This paper attempts to examine how financial characteristics affect the performance of Investor- Owned Firms (IOF) and Unions of Agricultural Cooperatives (UAC) in Greece. Data has been collected over a period of five years for IOF (1995-1999) and six years for UAC (1995-2000). A theoretical model within a System of four simultaneous equations presenting size, profitability, financial risk and business risk as dependent variables has been developed. Financial analysis results were used with the help of OLS, panel data (fixed effect - random effect models), SUR and 3SLS techniques, to estimate those parameters which would determine the profit performance of the IOF and the UAC as well as to compare and contrast their financial structure and policies.
83. EAAE Seminar on Food Quality Products in the Advent of the 21st Century: Production, Demand and Public Policy, 2003/09/04-07, Chania (Greece)